Review on Application of BIM in Architecture, Engineering and Construction (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Building Information Modeling (BIM) has emerged as a transformative paradigm in the field ofarchitecture, engineering, and construction (AEC). This review paper provides a comprehensive analysisof the evolution, applications, benefits, challenges, and future prospects of BIM. The paper begins bytracing the historical development of BIM from its origins as a digital drafting tool to its current status as acollaborative and data-driven process for designing, constructing, and managing built environments.